Metode Field Trip dalam Pembelajaran Sejarah Lokal Materi Sejarah Kesultanan Palembang Darussalam - Desita, Aulia (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
This paper examines the results of the field trip learning method for 7th grade students of Al Azhar 33 Palembang Islamic Junior High School in the Social Science subject of Kesultanan Palembang Darussalam Local History. The formulation of the problems in this study are: (1) How to increase local history knowledge to students?, (2) What are the factors that cause field trip learning methods to increase local history knowledge in students?, (3) How can field trip learning methods be used to increase local history knowledge in students? This type of research is descriptive research using a qualitative approach, the data collection technique uses several methods, namely: observation, interviews, and documentation. The results of this research show that: (1) increasing students' local history knowledge by applying learning methods that can attract students' interest in learning so that history learning becomes more alive and teachers do not only provide cognitive knowledge in the classroom, (2) the factors that cause the field trip learning method can be used to increase students' knowledge is a learning method that can be used by teachers to facilitate students to learn directly at the location or scene not only the theory in the book, so that students get a concrete, effective and interesting learning experience, (3) The field trip learning method invites students to see the reality that exists regarding the Kesultanan Palembang Darussalam e at the Istana Adat Kesultanan Palembang Darussalam. The results showed an increase in the knowledge of students with local history material of the Kesultanan Palembang Darussalam as seen through informal and unstructured interviews with of 7th grade students of Al Azhar 33 Palembang Islamic Junior High School.